Matrix metalloproteinase-9 mediates hypoxia-induced vascular leakage in the brain via tight junction rearrangement - Bauer, Alexander Thomas; Bürgers, Heinrich; Rabie, Tamer; Marti, Hugo (Journal of cerebral blood flow & metabolism, 2010)
Blood-brain barrier (BBB) disruption, resulting from loss of tight junctions (TJ) and activation of matrix metalloproteinases (MMPs), is associated with edema formation in ischemic stroke. Cerebral edema develops in a phasic manner and consists of both vasogenic and cytotoxic components. Although it is contingent on several independent mechanisms, involving hypoxic and inflammatory responses, the single effect of prolonged hypoxia on BBB integrity in vivo was not addressed so far. Exposing mice to normobaric hypoxia (8% oxygen for 48 h) led to a significant increase in vascular permeability associated with diminished expression of the TJ protein occludin. Immunofluorescence studies revealed that hypoxia resulted in disrupted continuity of occludin and zonula occludens-1 (Zo-1) staining with significant gap formation. Hypoxia increased gelatinolytic activity specifically in vascular structures and gel zymography identified MMP-9 as enzymatic source. Treatment with an MMP inhibitor reduced vascular leakage and attenuated disorganization of TJ. Inhibition of vascular endothelial growth factor (VEGF) attenuated vascular leakage and MMP-9 activation induced by hypoxia. In conclusion, our data suggest that hypoxia-induced edema formation is mediated by MMP-9-dependent TJ rearrangement by a mechanism involving VEGF. Therefore, inhibition of MMP-9 might provide the basis for therapeutic strategies to treat brain edema.
Published online 9 December 2009
Gesehen am 07.12.2022